Sample collection of airborne microbial diversity and analysis of air quality in a brazilian school environment (Research, Society and Development, 2025)
Microorganisms are essential components of ecosystems, playing crucial roles in maintaining environmental, human, and animal health. In the context of public health and One Health, understanding the dynamics of these organisms in the environment is key to disease prevention and control. The present study aims to investigate the diversity of airborne bacteria in a school environment in Cuiabá, a city in the Midwest region of Brazil, using the impingement on solid technique. Air samples were collected from indoor and outdoor locations, including a bathroom, cafeteria, teachers' lounge, reception area, classroom, and an outdoor sports court. At each site, two Petri dishes were exposed for 15 minutes. The samples were then incubated for 48 hours at a controlled temperature of 37°C, followed by morphological analysis and microscopic examination. Unexpectedly, outdoor areas, particularly the sports court, showed higher bacterial concentrations, to the common assumption of higher microbial loads in enclosed spaces due to limited ventilation. This finding suggests that even naturally ventilated areas require more careful analysis to ensure air quality in public spaces. Additionally, fungal growth was observed in two samples, further highlighting potential environmental risks. These results underscore the importance of improving hygiene strategies, and management in school settings to mitigate health risks associated with airborne microorganism exposure.